Analisis Nilai Tambah Usaha Pengolahan Ikan Belida Menjadi Kerupuk Di Kelurahan Kemalaraja Kecamatan Baturaja Timur Kabupaten OKU - Ary Eko Prastya Putra (Jurnal Bakti Agribisnis, 2019)
The objectives of this study were to: 1) determine the amount of income obtained from processing belida fish into crackers in Kemalaraja Village, East Baturaja District, OKU Regency, 2) determine the amount of added value obtained from processing belida fish into crackers in Kemalaraja Village, East Baturaja District, Regency OKU. The results showed that the income obtained in the business of processing belida fish into crackers in Kemalaraja Village, East Baturaja District, OKU Regency is Rp. 549,288 / average production, while the added value generated in the business of processing belida fish into crackers in Kemalaraja Village, East Baturaja District, Regency OKU is IDR 627,465 / production average, and the added value per kg is IDR 38,128.